Implementation Of Flexible Working Arrangements: An Insights from A Multinational Corporation In Malaysia - Mohd Isa, Salmi; Musa, Mazidah; Abdul Rashid, Mimie (2016)
One would tend to think that an international banking group that has had years of previous experience in carrying out flexible working arrangements (FWA) in its 1,200+ branches worldwide would have it easy in implementing what seems like a tried-and-true system in its wholly-owned subsidiary in Malaysia. The answer might surprise you: apparently, FWA does not go by the one-size-fits-all model. EastAsia Bank* (*not its real name), is a wholly owned subsidiary of an international bank that has a presence in more than 70 countries. True to its claim of upholding diversity and inclusion and promoting practices that improve work-life balance, EastAsia Bank been implementing two forms of FWA since 2011 and 2012, respectively, with the first form being flexible hours – an arrangement where employees have flexible starting and ending times at work – and the second form being a “Work From Home” (WFH) programme that allows its employees, as a standard, to work from home at least one day each week. EastAsia Bank’s parent company has been successfully implementing these two forms of FWA – with the addition of part-time work – in its other offices in various parts of the world since 2007. It has developed, invested in, and refined, over the years, a solid system and infrastructure for its FWA programmes, which includes the appropriate hardware and software that allows its employees to work from home within the security of the company’s virtual private network (VPN). A case study method has been conducted to examine how EastAsia Bank could successfully implement in Malaysia the exact same model that has previously met success in its other offices around the world. Surprisingly, such is not the case.